The Influence of Lifestyle and Financial Literacy on Financial Behavior: The Mediating Role of Financial Knowledge among Employees of the Bali Regional Police - Mustika Putri, Nyoman Ayu; Bagus Gunadi, I Gusti Ngurah; Gregorius Paulus Tahu (International Journal of Economics and Management Sciences, 2026)
This study aims to analyze the effects of lifestyle and financial literacy on financial behavior, with financial knowledge serving as a mediating variable among employees of the Bali Regional Police (Polda Bali). The study is motivated by the importance of effective financial management among employees, as lifestyle patterns and levels of financial literacy may significantly influence financial behavior. Financial knowledge is considered a crucial factor that enhances individuals’ ability to make informed, responsible, and sustainable financial decisions.The population consisted of all employees of Polda Bali, with a sample of 99 respondents determined using the Slovin formula. This study employed a quantitative research approach using primary and secondary data sources. Data were collected through questionnaires, interviews, and documentation. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among the variables. The findings indicate that lifestyle has a negative and significant effect on both financial behavior and financial knowledge, whereas financial literacy has a positive and significant effect on financial behavior and financial knowledge. In addition, financial knowledge positively and significantly influences financial behavior. The mediation analysis reveals that financial knowledge partially mediates the relationship between lifestyle and financial behavior, as well as the relationship between financial literacy and financial behavior among employees of the Bali Regional Police. These results highlight the importance of improving financial literacy and financial knowledge to foster better financial behavior.